Satai Dance As A Representation Of Barimou Perulai In The Koto Tuo Community Of Jambi Province : Tari Satai Sebagai Representasi Barimou Perulai Pada Masyarakat Koto Tuo Provinsi Jambi - Ulfa, Resa; MD, Slamet (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Traditional dances are vital expressions of communal identity and cultural continuity. Specific Background: In the Koto Tuo community of Jambi Province, Satai Dance is widely recognized as a welcoming performance, yet its deeper origin as a ritual rooted in the Barimou Perulai tradition—aimed at spiritual protection for pregnant women—remains understudied. Knowledge Gap: Existing literature often focuses on choreographic elements but lacks analysis of symbolic cultural representation. Aims: This study aims to explore how Satai Dance functions as a symbolic reconstruction of Barimou Perulai, articulating identity and spirituality within the Koto Tuo society. Results: Through qualitative ethnographic methods and dance anthropology, findings reveal that the dance encapsulates layers of meaning through movement, music, costumes, and props that reflect sacred values, communal solidarity, and local cosmology. Novelty: This research offers a new anthropological lens on Satai Dance by framing it as a triadic representation—reflective, intensional, and constructionist—of cultural heritage, as conceptualized by Stuart Hall. Implications: The study underscores the dance’s function not only as cultural preservation but as a communicative tool for transmitting moral, social, and spiritual values, supporting its integration in education, cultural policy, and identity formation efforts.Highlight : Satai Dance serves not only as performance art but as a representation of the spiritual and social values rooted in the Barimou Perulai tradition. The dance incorporates symbolic elements—movement, costume, music, and properties—that reflect the cultural identity of the Koto Tuo community. It plays a vital role in preserving local heritage amid the pressures of modernization and globalization. Keywords : Satai Dance, Barimou Perulai, Cultural Representation, Koto Tuo Community, Dance Anthropology